Can serum ferritin be employed as prognostic marker of pediatric septic shock and severe sepsis? - Mihir Sarkar; Satyabrata Roychowdhury; Mohammad Asraf Uz Zaman; Sumantra Raut; Subhajit Bhakta; Mousumi Nandy (Wolters Kluwer Medknow Publications, 2021)
Introduction: Serum ferritin has emerged as an independent marker predicting the outcome of critically ill patients. The cutoff value of ferritin in predicting mortality in septic children is not well established. Objective: The aim is to determine the cutoff value of ferritin which is, best predictive of mortality in patients with age from 1 month to 12 years with a diagnosis of septic shock or severe sepsis and to evaluate correlation with PRISM III score, and Pediatric Logistic Organ Dysfunction score (PELODS). Materials and Methods: A prospective observational study was conducted over a period of 2 years at pediatric intensive care unit (PICU) in children with age from 1 month to 12 years with septic shock or severe sepsis and PICU stay >24 h. Children with autoimmune diseases, primary hemophagocytic lymphohistiocytosis, blood transfusion in the past 4 months, known malignancies and immunosuppressive treatment were excluded. PRISM-III and PELODS were assessed to predict the risk of mortality and severity of disease. The highest value of ferritin was taken to draw area under the curve using receiver operating characteristic curve and determine cutoff value. Results: Out of 176 children of septic shock or severe sepsis, 132 were included in the study. Mortality rate was 22.7% (n = 30). PRISM III and PELODS-2 were significantly high in nonsurvivors (P ≤ 0.001 and 0.006, respectively). The cutoff value of ferritin at 2375 ng/dl had sensitivity 96.7% and specificity 88% to predict mortality. Ferritin level was positively correlated to the PRISM III and PELODS, correlation coefficient 0.447 and 0.601, respectively. Conclusion: Serum ferritin values ≥2375 ng/mL in children with septic shock, and severe sepsis was significantly associated with mortality. Its performance had a good correlation with PRISM III and PELODS.